Hepatic farnesoid X receptor protein level and circulating fibroblast growth factor 19 concentration in children with NAFLD. (18th August 2017) - Nobili, Valerio; Alisi, Anna; Mosca, Antonella; Della Corte, Claudia; Veraldi, Silvio; De Vito, Rita; De Stefanis, Cristiano; D'Oria, Valentina; Jahnel, Joerg; Zohrer, Evelyn; Scorletti, Eleonora; Byrne, Christopher D.
Abstract: Background & Aims: Treatment with the farnesoid X receptor (FXR) agonist obeticholic acid is ineffective in some patients with non‐alcoholic steatohepatitis (NASH) but the explanation is uncertain. We investigated hepatic FXR expression, and measurements of fibroblast growth factor 19 (FGF19) and bile acids (BAs) in children with NAFLD to investigate relationships with NASH. Methods: 33 children with NAFLD who underwent diagnostic liver biopsy were studied. Hepatic FXR protein levels and circulating FGF19 concentrations were compared with those analysed in five control subjects with proven normal liver histology. NASH was defined by the Paediatric NAFLD Histological Score (PNHS). Binary logistic regression with adjustment for covariates and potential confounders was undertaken to test factors independently associated with: a) NASH and b) hepatic FXR protein levels. Results: Mean ± SD age was 13.7 ± 1.9 years. Nineteen patients had NASH (PNHS ≥ 85) and 14 did not have NASH (PNHS < 85). Hepatic FXR level and plasma FGF19 concentration varied 10‐fold and 5‐fold, respectively, between groups, and was highest in control subjects, intermediate in NAFLD without NASH, and lowest in NASH (between group differences P < .001 and P < .01 respectively). NASH was independently associated with both FXR protein levels (OR = 0.18, 95% CI 0.09, 0.38) and FGF19 concentration (OR = 0.55, 95% CI 0.20, 0.89). Conclusions: FXR protein levels vary markedly between normal liver, NAFLD without NASH, and NASH. Low levels of FXR are independently associated with NASH.